Effects of hybrid and bacterial inoculation on fermentation quality and fatty acid profile of barley silage. (15th September 2017) - Kim, Dong Hyeon; Amanullah, Sadar M.; Lee, Hyuk Jun; Joo, Young Ho; Han, Ouk Kyu; Adesogan, Adegbola T.; Kim, Sam Churl
Abstract: This study estimated the effects of hybrid and bacterial inoculant on fermentation quality and fatty acid profile of barley silages. Yuyeon (Silkless) and Youngyang (Silking) barley hybrids were harvested at 24.9 and 27.1% dry matter, respectively, and chopped to 10 cm lengths. Each hybrid was treated with or without an inoculant (2 × 10 4  colony‐forming units/g of Lactobacillus plantarum ). A total of 48 silos were prepared in an experiment with a 2 × 2 (hybrid × inoculant) treatment arrangement with four replications and three ensiling durations (2, 7 and 100 days). After 100 days of ensiling, Yuyeon silage had higher ( P  <   0.05) in vitro dry matter digestibility and C18:3n‐3 than Youngyang silage. Youngyang silage had higher ( P  <   0.05) acetic acid and C18:2n‐6 than Yuyeon silage. Inoculation reduced the C18:3n‐3 concentration of both hybrids and increased ( P  <   0.05) the C18:2n‐6 of Youngyang. However, fermentation quality was not improved by the inoculant. These results indicate that Yuyeon hybrid might have better potential benefits on animal performances due to its smooth awn and silkless nature, and higher in vitro dry matter digestibility. Its higher C18:3n‐3 would be better for improving fatty acid profile of meat or milk than Youngyang hybrid.